The Analysis of the Culture-Related Contents in an Indonesian English Textbook - Ulya Safira Riadini; Bambang Yudi Cahyono (IJELTAL (Indonesian Journal of English Language Teaching and Applied Linguistics), 2021)
This research analyzed the presentation of culture-related contents of the tenth-grade senior high school English textbook. The textbook was published by the Ministry of Education and Culture of Republic Indonesia. The written texts that contain cultural information were identified by employing content analysis based on Cortazzi & Jin (1999) three sources of cultural information, and coded under the eight categories by Byram (1993). Cortazzi & Jin (1999) categorization is used to portray the presentation of culture-related contents in the English textbook. The written texts were classified into those sources, and Byram (1993) checklist was used in the procedure of the content analysis mentioned earlier. The scope of the cultural content and how it meets the needs of cultural teaching in English language teaching are revealed in this checklist. The findings showed that the EFL textbook not only reflects the target cultures, but also source cultures and international cultures. The materials present source cultures as the most frequently depicted cultures and the international cultures are the least frequently depicted cultures. In conclusion, the materials related to culture in this English textbook are well represented to be integrated into the English language teaching and learning process.